Highly photocytotoxic silicon(IV) phthalocyanines axially modified with l-tyrosine derivatives: Effects of mode of axial substituent connection and of formulation on photodynamic activity. (June 2017) - Sun, Qun; Zheng, Bi-Yuan; Zhang, Yan-Hong; Zhuang, Jing-Jing; Ke, Mei-Rong; Huang, Jian-Dong
Abstract: Three novel silicon(IV) phthalocyanines (SiPcs) axially substituted withl -tyrosine moieties possessing different modes of connection have been synthesized and characterized. The ester-linked SiPc3 shows a slight red-shift of Q band, higher fluorescence emission and photosensitizing efficiency relative to the ether-linked SiPcs1 and2 . However, SiPcs1 and2 exhibit more potent photocytotoxicity than SiPc3, due to higher cellular uptake. When formulated with Cremophor EL™, all SiPcs show very high photocytotoxicity toward HepG2 cells, particularly for SiPc2 which has a low IC50 value (1.3 nM). In the case of the phosphate buffered saline formulation, the photodynamic activities follow the trend1  > 2 >>3, which is different with that formulated with Cremophor EL™ (2  > 1  > 3 ). Thus, varying the mode of attachment ofl -tyrosine moieties on the axial positions of SiPcs affects their photophysical and photochemical properties, and biological behavior. Graphical abstract: Highlights: Three SiPcs were modified with tyrosine derivatives through ester or ether bond. The photophysical and biological properties are affected by the connection mode. The SiPc2 shows extremely high photocytotoxicity with an IC50 value of 1.3 nM. Cremophor EL takes different effects on photocytotoxicity of these compounds.